Causes of attrition among lecturers in colleges of education in North East, Nigeria - Bello, Umar, M.; Abdullahi, Umar (Kashere Journal of Education, 2023)
The main purpose of the study was to assess the Causes of Attrition among Lecturers in Colleges of Education in North Eastern Nigeria. Specifically, the study sought to determine the Impact of Work Condition on Attrition among Teaching Staff in the study area. A research question in line with the stated objective guided the study. The study employed survey research design where data collected was analyzed using mean. Finding of the study reveals that work condition is a factor that causes attrition among lecturers in Colleges of Education. The study recommends that government should do everything humanly possible in ensuring that the work condition for lecturers in Colleges of education is conducive, just and supportive for active participation.